2014
DOI: 10.1155/2014/142546
|View full text |Cite
|
Sign up to set email alerts
|

Concern and Risk Perception: Effects on Osteoprotective Behaviour

Abstract: This study aimed to determine the effect that level of concern for osteoporosis, as well as self-perceived risk of osteoporosis and fracture, has on supplementation use, seeking medical advice, bone mineral density (BMD) testing, and antiosteoporosis medication (AOM) use. Study subjects were 1,095 female Australian participants of the Global Longitudinal study of Osteoporosis in Women (GLOW) untreated for osteoporosis at baseline. Study outcomes from self-administered questionnaires included calcium and vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…This concurs with findings from a crosssectional analysis of GLOW where women with higher SPR were more likely to report AOM use than women with lower SPR [5]. Barcenilla-Wong et al also reported that elevated self-perceived risk of fracture increases the likelihood of taking AOM prospectively [7].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This concurs with findings from a crosssectional analysis of GLOW where women with higher SPR were more likely to report AOM use than women with lower SPR [5]. Barcenilla-Wong et al also reported that elevated self-perceived risk of fracture increases the likelihood of taking AOM prospectively [7].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, it was previously demonstrated in GLOW that SPR of fracture does capture some aspect of fracture risk not currently measured using the conventional fracture prediction tool FRAX [5]. The perception of personal risk has been shown to modify an individual's behaviour related to their bone health [5,7]. Heightened self-perceived risks of osteoporosis and fracture significantly increases the likelihood of seeking medical advice hence, increasing the chances, in appropriate individuals, of being given a diagnosis of osteoporosis-a well known predictor of treatment initiation [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed that the level of perception about the disease might modify individual behavior [21,22]. The Health Belief Model has confirmed that high perceptions provide an impetus to adopting health-protective behaviors [23]. Therefore, the perception of osteoporosis can positively impact people's lifestyles and behavior.…”
Section: Discussionmentioning
confidence: 99%